Textbook of Plastic and Reconstructive Surgery - E. Butler, Peter; Ghali, Shadi; K. Kalaskar, Deepak (UCL Press, 2016)
Written by experts from London's renowned Royal Free hospital, Textbook of Plastic and Reconstructive Surgery offers a comprehensive overview of the vast topic of reconstructive plastic surgery and its various subspecialties for introductory plastic surgery and surgical science courses. The book comprises five sections covering the fundamental principles of plastic surgery, cancer, burns and trauma, paediatric plastic surgery and aesthetic surgery. Additional coverage of areas in which reconstructive surgery techniques are called upon includes abdominal wall reconstruction, ear reconstruction and genital reconstruction. The broad scope of this volume makes this a unique contribution to the field. Heavily illustrated throughout, Textbook of Plastic and Reconstructive Surgery is essential reading for anyone interested in furthering their knowledge of this exciting field.